Factors Influencing Low Participation of Catholic Youth in Spiritual Activities at St. Mikhael Kotabaru Parish - Mariana Goma; Petrus Tukan; Yosep Belen Keban (International Journal of Christian Education and Philosophical Inquiry, 2025)
This study aims to analyze the factors influencing the low participation of Catholic Youth in spiritual activities at St. Mikhael Kotabaru Parish. The research used a qualitative approach with a descriptive design to obtain an in-depth understanding of the phenomenon. Research subjects consisted of one Catholic Youth coordinator and six members selected purposively to represent diverse perspectives. Data collection techniques included unstructured interviews, participatory observation, and documentation. The data were then analyzed using the Miles and Huberman interactive model, which involves data reduction, data display, and conclusion drawing. The findings reveal that the low participation of Catholic Youth is influenced by both internal and external factors. Internal factors include low motivation, shyness, lack of self-confidence, unstable physical conditions, and the excessive use of social media, which often distracts youth from engaging in church life. Meanwhile, external factors consist of economic limitations, heavy school and work commitments, insufficient mentoring from religious leaders, negative peer influence, and minimal family support. These challenges collectively contribute to the declining interest and active involvement of Catholic Youth in spiritual activities. This research highlights the urgency of creating innovative spiritual activity programs that are more attractive and relevant to the needs of young people in the current era. In addition, optimizing mentoring and guidance from parish leaders, parents, and peers is crucial to strengthen motivation and a sense of belonging among Catholic Youth. By addressing both internal and external factors simultaneously, the church community can foster a more participative and dynamic youth movement. Therefore, strategic collaboration among religious leaders, families, and the youth themselves is essential in revitalizing Catholic Youth participation in church life.